Cognitive disorders in normal pressure hydrocephalus with initial parkinsonism in comparison with de novo Parkinson's disease. (3rd September 2018) - Picascia, M.; Pozzi, N. G.; Todisco, M.; Minafra, B.; Sinforiani, E.; Zangaglia, R.; Ceravolo, R.; Pacchetti, C.
Abstract : Background and purpose: The clinical differentiation between parkinsonism in idiopathic normal pressure hydrocephalus (iNPH) and Parkinson's disease (PD) remains challenging in the initial phase. Whether an early cognitive profiling might support the differential diagnosis of early iNPH and PD was addressed. Methods: Neuropsychological tests of 40 iNPH subjects with early symptoms resembling parkinsonism were retrospectively evaluated together with 47 de novo PD patients (dnPD). Only neuropsychological tests performed within 1 year from the first motor symptom were included. The cognitive spectrum of iNPH and dnPD was also compared with a sample of 70 normal controls. Results: A clear difference in the cognitive profile of iNPH, dnPD patients and normal controls was shown. 65% of iNPH subjects showed a diffuse cognitive impairment, including memory, visuospatial abilities, fronto‐executive functioning and attention, whereas only 25.5% of the dnPD patients presented an executive dysfunction. 35% of iNPH and 74.5% of PD patients performed within the normal range ( P < 0.05). Conclusion: Subjects with iNPH showed an early and diffuse alteration of cognition with respect to dnPD patients. Performing a prompt and accurate neuropsychological evaluation might support the differential diagnosis of these two conditions of parkinsonism.